If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3p + 4) = -2p + 6 Reorder the terms: -1(4 + 3p) = -2p + 6 (4 * -1 + 3p * -1) = -2p + 6 (-4 + -3p) = -2p + 6 Reorder the terms: -4 + -3p = 6 + -2p Solving -4 + -3p = 6 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. -4 + -3p + 2p = 6 + -2p + 2p Combine like terms: -3p + 2p = -1p -4 + -1p = 6 + -2p + 2p Combine like terms: -2p + 2p = 0 -4 + -1p = 6 + 0 -4 + -1p = 6 Add '4' to each side of the equation. -4 + 4 + -1p = 6 + 4 Combine like terms: -4 + 4 = 0 0 + -1p = 6 + 4 -1p = 6 + 4 Combine like terms: 6 + 4 = 10 -1p = 10 Divide each side by '-1'. p = -10 Simplifying p = -10
| x+4=3x+26 | | 3d-5n-4= | | 9m-14=49 | | 3y+5-8y=-55 | | 2n-3=5n | | 33075x=-14179 | | -3.5-5(2.5x-3x^2)=-10.5-3(4.5x-5x^2) | | -7+x=4x-7 | | 75.00+0.1x=400.00 | | 14x^3-18x^2-10x= | | 3m+8=35 | | x^4-i=0 | | -3+5x=-3x+45 | | x^4+i=0 | | y=1200x-42000 | | 7x^2+2x-5= | | 3(4s+9)=135 | | 4x-4=18-7x | | (10-6i)=(9-3i) | | 4(2l+3)=60 | | 2(a-6)=28 | | 3p-11=7 | | 4x+8y=60 | | u-6*9=63 | | P=n-0.1n+150 | | -5n=7n-5.5 | | q-3*2=20 | | 6=8y-4y-2 | | 10(-2)-y=15 | | 8x+.75=2 | | (e+3)*2=16 | | 5a+2a=35 |